Avaliação da atividade antimicrobiana de plantas utilizadas na medicina popular da Amazônia - RIBEIRO, Christian Miranda (2008)
The study of medicinal plants it makes possible the discovery of new bioactive components in the search for promising drugs. The increase of infections and the appearance of the microbial resistance strengthen this research. The Objective of this study it was evaluate the antimicrobial activity of the extracts of six medicinal plants of the Amazonia: Psidium guajava (guava), Bryophyllum calycinum Salisb (pirarucu), Eleutherine plicata Herb (marupazinho), Uncaria guianensis (Cats claw), Arrabideae chica (pariri) e Mansoa alliacea (Lam.) A.H. Gentry (cipó d'alho) against ATCC strains of fungi and bacteria.The collection and the identification of the plant were performed in EMBRAPA/CPATU and the phytochemical analysis in the Laboratory of FACFAR/UFPA and CESUPA in agreement with the methodologies established in these laboratories. The crude ethanolic extract of leaves and the underground parts of marupazinho were submitted to the antimicrobial activity evaluation though the ágar disc diffusion method and determination of minimum inhibitory concentration (MIC) though microdilution in plate and ágar disc diffusion methods. The extracts were used in concentrations of 500, 250, 125, 62,5 and 31,25 mg/mL using as solvent Dimethyl Sulfoxide (DMSO). The Guava extract was effective against S. aureus, P. aeruginosa and C. albicans (MIC 125mg\mL), pirarucu was effective against S aureus (MIC= 500 mg/mL) and P. aeruginosa (MIC= 250 mg/mL), marupazinho against S.aureus (MIC= 500mg/mL) and C. albicans (MIC= 250mg/mL), Cats claw against S. aureus (MIC= 62,5mg/mL) and pariri was effective against S. aureus (MIC= 62,5 mg/mL), E. coli (MIC=250 mg/mL) and C. albicans (MIC 500 mg/mL). The fractions of U. guianensis extracts was obtained though fractioned dissolution methods and show that only the methanolic fraction presented antimicrobial activity. The results show that Amazonia medicinal plants presents antimicrobial activity and. This promissory extracts open the possibility of finding new clinically effective antimicrobial compounds.